(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
In this situation, the success of teaching the Russian language to primary school children in certain regions of the Republic of Uzbekistan depends not only on the individual age characteristics of students and the peculiarities of the manifestation of national identity, but also on the learning conditions, i.e. on the pedagogical skills of the teacher himself.